Nonempirical calculations of NMR indirect spin-spin coupling constants. Part 14 azomethines of the alpha, beta-unsaturated aldehydes - Krivdin, Leonid B (Magnetic resonance in chemistry : MRC, 2006)
Copyright 2005 John Wiley & Sons, Ltd.